Die Ausbeutung der Kriegsgefangenen in der Industrie und Landwirtschaft 1939 - 1945 am Beispiel Oberschlesiens [The exploitation of prisoners of war in industry and agriculture 1939 - 1945 using the example of Upper Silesia] - Szefer, Andrzej (Studia Historiae Oeconomicae, 1979)
This article examines the exploitation of prisoners of war by the Nazi regime in industry and agriculture in Upper Silesia between 1939 and 1945. The analysis focuses on the Cieszyn (Teschen) Stalag, one of the most important POW camps in Wehrkreis VIII, which from 1943 onward served as a central labor reservoir for the Upper Silesian war economy. The aim of the study is to present the scope, organization, and consequences of POW labor deployment in Upper Silesia. The author draws on extensive sources from the Military Archive in Prague, as well as statistical data, reports from camp commandants, and labor offices. The study highlights the role of various nationalities (including Russians, British, Italians, Yugoslavs, and French) in different economic sectors, especially mining, industry, and transport. The findings show that by January 1945, nearly 60,000 prisoners were deployed in 254 labor detachments in the Katowice administrative district - over 90% of them in industry and mining. Labor conditions were extremely harsh: long working hours, inadequate food, lack of medical care, and frequent violations of the Hague and Geneva Conventions. The situation was particularly dire for Soviet POWs, who suffered from especially high mortality and accident rates. Their daily life was marked by forced productivity, disciplinary measures, arbitrary punishments, and food ration reductions. The analysis documents that the Nazis viewed POWs as cheap, expendable labor, and that their exploitation intensified as the war progressed. The wartime industrial output of Upper Silesia relied heavily on this inhumane system.